Meningkatkan Kompetensi Guru PAUD Dalam Penyususnan Modul Ajar Berbasis Parental Involvement - Ismi, Lailatul; Fitriani, Rohyana; Adawiyah, Rabihatun (Shofanah Media Berkah, 2025)
PKM aims to improve the skills of early childhood educators in preparing teaching modules based on parental involvement at the level of Early Childhood Education (PAUD). This service is carried out because the teaching module plays a very important role in the implementation of quality Early Childhood Education. In addition, researchers found that many schools when carrying out parenting activities do not provide many guidebooks as guidelines for parents to understand parenting material in stimulating various aspects of Child Development. Parenting materials delivered during parenting activities also have not focused on aspects of social emotional development which is one of the most important aspects to be developed in children from an early age. In addition, several factors were found to cause lack of stimulation in the aspect of social emotional development in children including: First, limited knowledge related to the preparation of social emotional material to develop teaching modules. Second, the lack of role of parents in providing care, especially in stimulating the social emotional development of children, because basically parents have a great influence in stimulating the social emotional development of children. If parents do not set a good example, lack attention, or are not involved in educating children positively, then the child's development can be neglected. Social emotional development during the golden age is the spearhead that determines attitudes, values, and behavior in the future. The implementation of The Independent curriculum has become the main focus in improving the quality of education at the PAUD unit level. One of the most important aspects in the implementation of The Independent curriculum in early childhood education is the mentoring activities for the preparation of teaching modules. A well-structured teaching module can be an effective guideline for educators and parents in providing a better and enjoyable learning experience for children. Mentoring in the preparation of teaching modules in early childhood education is important because the module is a tool that is needed by educators and parents in the teaching process. Teaching modules can help educators to design learning activities that match the characteristics and developmental needs of early childhood. With mentoring, educators can get in-depth guidance on how to develop modules that explore the child's potential and stimulate aspects of Child Development and integrate principles into the curriculum used. The importance of mentoring activities in the preparation of teaching modules is also related to efforts to improve the quality and relevance of learning in early childhood education, especially in parenting activities carried out to support the success of children's education. With assistance, the preparation of modules can be more targeted, accommodate the diversity of learners, and ensure that learning materials in accordance with the development and needs of children.